Higher Education amid Crisis in Sri Lanka - Vivekanantharasa , Raveenthiran; Blanco, Gerardo (International Higher Education, 2022)
The current economic and social crisis in Sri Lanka has caused many challenges in the national higher education system. Despite much effort and investment, all aspects of higher education in the country, including teaching and learning, funding, facilities, and access, have been severely affected, creating significant uncertainty for the future.